Challenges Faced by Digital Immigrant Nurse Educators in Adopting Flexible Learning Options During the COVID-19 Pandemic: A Phenomenological Study - Hamdoni Pangandaman (Iran University of Medical Sciences, 2023)
Background: The COVID-19 pandemic has compelled many educational institutions to employ flexible learning options (FLO), requiring technology integration in teaching. Digital immigrant nurse educators, who are educators born before 1985, may need help adopting FLO due to their limited technological knowledge and skills. This study explores the challenges digital immigrant nurse educators face in adopting FLO as a teaching strategy during the COVID-19 pandemic. Methods: Employing a qualitative phenomenological research approach, we researched 6 digital immigrant nurse educators with at least 10 years of teaching experience in the nursing institution at the College of Health Sciences of Mindanao State University in Marawi City, Philippines. These educators, expressing difficulty in adopting FLO, were purposively selected and interviewed from October 2021 to April 2022. Interviews were conducted through a scheduled Zoom meeting. For this purpose, an interview guide with open-ended questions was used. Colaizzi's method of analysis was applied to analyze the data. Results: We identified 4 themes representing the challenges digital immigrant nurse educators face in adopting FLO. The themes comprised a lack of technological knowledge and skills, difficulty adjusting to new teaching methods, inadequate technological resources, and emotional stress and exhaustion. Conclusion: Given the challenges experienced by Filipino digital immigrant nurse educators in integrating FLO amid the pandemic, this study recommends providing support and resources to improve these nurse educators' technical knowledge and skills. Continuous education is crucial for successfully integrating FLO into their teaching practices.